2005
DOI: 10.1155/jbb.2005.242
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic and Cytotoxic Studies of Beta‐Sitosterol and Pteropodine in Mouse

Abstract: Beta-sitosterol (BS) and pteropodine (PT) are constituents of various plants with pharmacological activities potentially useful to man. The chemicals themselves possess biomedical properties related to the modulation of the immune and the nervous systems, as well as to the inflammatory process. Therefore, safety evaluation of the compounds is necessary in regard to their probable beneficial use in human health. The present study evaluates their genotoxic and cytotoxic potential by determining the capacity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 22 publications
3
35
0
Order By: Relevance
“…Mortality among mice was observed up to 7 days; the LD 50 was obtained as the geometric mean between the minimal lethal dose and the maximal sublethal dose. With this procedure we confirmed the previously reported LD 50 of 771 mg/kg for pteropodine [16].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Mortality among mice was observed up to 7 days; the LD 50 was obtained as the geometric mean between the minimal lethal dose and the maximal sublethal dose. With this procedure we confirmed the previously reported LD 50 of 771 mg/kg for pteropodine [16].…”
supporting
confidence: 90%
“…Based on the abovementioned information, our laboratory has undertaken the evaluation of the genotoxic and antigenotoxic potential of β‐sitosterol and pteropodine. In an earlier study, we found that neither of the two compounds produced genotoxicity in mouse [16]. We have also determined that β‐sitosterol protects mouse cells from the DNA damage induced by doxorubicin, and that it is a lymphocyte inducer and a free radical scavenging agent [17].…”
mentioning
confidence: 99%
“…; Paniagua‐Pérez et al . ) and are used in foods already. However, other potential gelators may not have the required approval to be used as direct ingredients in foods in the amounts that are necessary to form an organogel; therefore, certain regulatory changes will be needed to enable this process.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that: (i) cassipourol exhibits cytotoxicity with IC 50 values of 2.4 and 2.8 μg/mL (8.2 and 9.5 µM) against the A2780 human ovarian cancer cell line [21] and larvicidal activity against Culex quinquefasciatus [57]; (ii) the cytotoxicity of α-amyrin has not been reported yet conversely to its anomer β-amyrin which exhibited weak cytotoxic activities against human bladder cancer cells (NTUB1) [58]; and (iii) β-sitosterol is already used and commercialized as dietary supplement without genotoxicity and cytotoxicity [59]. …”
Section: Discussionmentioning
confidence: 99%